Assessment of type I interferon signatures in undifferentiated inflammatory diseases: A Japanese multicenter experience - Miyamoto, Takayuki; Honda, Yoshitaka; Izawa, Kazushi; Kanazawa, Nobuo; Kadowaki, Saori; Ohnishi, Hidenori; Fujimoto, Masakazu; Kambe, Naotomo; Kase, Naoya; Shiba, Takeshi; Nakagishi, Yasuo; Akizuki, Shuji; et al. (Frontiers in Immunology, 2022)
Purpose Upregulation of type I interferon (IFN) signaling has been increasingly detected in inflammatory diseases. Recently, upregulated IFN signature has been suggested as a potential biomarker to identify IFN-driven inflammatory diseases. Yet, it remains unclear to what extent type Ⅰ IFN is involved in the pathogenesis of undifferentiated inflammatory diseases. This study aimed to quantify the type Ⅰ IFN signature in clinically undiagnosed patients and assess clinical characteristics in those with a high IFN signature. Methods A type Ⅰ IFN signature was measured in patients’ whole blood cells. Clinical and biological data were collected retrospectively, and an intensive genetic analysis was performed in undiagnosed patients with a high IFN signature. Results A total of 113 samples from 94 patients with inflammatory diseases, including 37 undiagnosed cases, were analyzed. Increased IFN signaling was observed in 19 undiagnosed patients, with ten exhibiting clinical features commonly found in type Ⅰ interferonopathies. Skin manifestations, observed in eight patients, were macroscopically and histologically similar to those found in proteasome-associated autoinflammatory syndrome. Genetic analysis identified novel mutations in the PSMB8 gene of one patient, and rare variants of unknown significance, in genes linked to type Ⅰ IFN signaling, in four patients. A JAK inhibitor effectively treated the patient with the PSMB8 mutations. Patients with clinically quiescent idiopathic pulmonary hemosiderosis and A20 haploinsufficiency showed enhanced IFN signaling. Conclusions Half of the patients examined in this study, with undifferentiated inflammatory diseases, clinically quiescent A20 haploinsufficiency, or idiopathic pulmonary hemosiderosis, had an elevated type Ⅰ IFN signature.